Hubungan Pengetahuan Dan Sikap Kader Terhadap Peran Kader Dalam Masyarakat Di Wilayah Kerja Puskesmas Sukarame Kota Bandar Lampung - Wahid Tri Wahyudi; M Ricko Gunawan; Feri Febri Saputra (Malahayati Nursing Journal, 2022)
ABSTRACT Achievement of standard growth monitoring activities in infants aged 0-59 months; ≥ 8 times in the last 12 months, in 2007 it was 45.4%, in 2013 it was 44.6% and in 2018 it was 54.6% (Kemenkes RI, 2018). Posyandu visit coverage is below the target of Sukarame Health Center by 60.4%, and is the puskesmas with the lowest D / s coverage in Bandar Lampung City. Kader acts as the spearhead of monitoring the growth of toddlers in the region where he lives, so the level of knowledge and skills of cadres becomes very important. To find out the relationship of knowledge and attitude of cadres towards the role of cadres in the community in the Working Area of Sukarame Health Center bandar Lampung City in 2020. A type of quantitative research, using a cross sectional approach. The population in this study is the entire cadre of Posyandu in the Sukarame Health Center Working Area of Bandar Lampung City numbering 160 people. A sample of 115 respondents. Using purposive sampling techniques. Data collection techniques are done using quesioners. The statistical test used is the chi square test. Respondents with bad knowledge are as many as 35 respondents (54.7%), positive attitudes that are as many as 36 respondents (56.3%), bad roles that are as many as 34 respondents (53.1%). There is a knowledge relationship to the role of cadres in society. There is a relationship of attitudes towards the role of cadres in the community in the Sukarame Health Center Working Area of Bandar Lampung City in 2020. There is a knowledge relationship to the role of cadres in the community in the Sukarame Health Center Working Area of Bandar Lampung City in 2020. There is a relationship of attitudes towards the role of cadres in the community in the Sukarame Health Center Working Area of Bandar Lampung City in 2020. Keywords: Knowledge, Attitudes, Role of Cadres ABSTRAK Pencapaian kegiatan pemantauan pertumbuhan yang sesuai standar yaitu pada bayi usia 0-59 bulan; ≥ 8 kali dalam 12 bulan terkahir, pada tahun 2007 adalah 45,4%, Tahun 2013 adalah 44,6% dan tahun 2018 adalah 54,6% (Kemenkes RI, 2018). Cakupan kunjungan Posyandu di bawah target yaitu Puskesmas Sukarame sebesar 60,4%, dan merupakan puskesmas dengan cakupan D/s terendah di Kota Bandar Lampung. Kader berperan sebagai ujung tombak dari pemantauan  pertumbuhan balita di wilayah tempat ia tinggal, sehingga  tingkat pengetahuan dan keterampilan kader menjadi hal yang sangat penting. Untuk mengetahui hubungan pengetahuan dan sikap kader terhadap peran kader dalam masyarakat di Wilayah Kerja Puskesmas Sukarame Kota Bandar Lampung  Tahun 2020. Jenis penelitian kuantitatif, menggunakan pendekatan cross sectional. Populasi pada penelitian ini adalah seluruh kader Posyandu di Wilayah Kerja Puskesmas Sukarame Kota Bandar Lampung berjumlah 160 orang. Sampel 115 responden. Dengan menggunakan teknik purposive sampling. Tehnik pengumpulan data dilakukan dengan  menggunakan quesioner. Uji statistik yang digunakan adalah uji chi square. Responden dengan pengetahuan tidak baik yaitu sebanyak 35 responden (54.7%), sikap positif yaitu sebanyak 36 responden (56.3%), peran tidak baik yaitu sebanyak 34 responden (53,1%). Ada hubungan pengetahuan terhadap peran kader dalam masyarakat. Ada hubungan sikap terhadap peran kader dalam masyarakat di Wilayah Kerja Puskesmas Sukarame Kota Bandar Lampung Tahun 2020. Ada hubungan pengetahuan terhadap peran kader dalam masyarakat di Wilayah Kerja Puskesmas Sukarame Kota Bandar Lampung Tahun 2020. Ada hubungan sikap terhadap peran kader dalam masyarakat di Wilayah Kerja Puskesmas Sukarame Kota Bandar Lampung Tahun 2020. Kata Kunci: Pengetahuan, Sikap, Peran Kade